1908
DOI: 10.1039/ct9089302016
|View full text |Cite
|
Sign up to set email alerts
|

CCI.—The coumarin condensation

Abstract: and others found t h a t phenols condense with ethyl acetoacetate and malic acid in t h e presence of concentrated sulphuric acid to form members of t h e coumarin series. Different phenols were found to condense with varying degrees of readiness; thus phenol, 0 -and p-cresols, quinol, and thymol gave extremely poor yields (phenol furnished not more than 3 per cent. of the theoretical quantity), but resorcinol, orcinol, and pyrogallol condensed very readily. Later, Pechmann (Bey., 1899, 32, 3681) showed t h a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1938
1938
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Pechmann with Kraft (157) and Graeger (155) extended this reaction to other phenols. Dey (64) condensed various phenols with acetonedicarboxylic acid ester and made a systematic study of the reactivity of the coumarin-4-acetic acids thus synthesized: Clayton (48) found that the phenols with alkyl, hydroxy, and dialkylamino groups in the positions marked X in the formulas given below undergo condensa-x^Noh V…”
Section: Azy /mentioning
confidence: 99%
“…Pechmann with Kraft (157) and Graeger (155) extended this reaction to other phenols. Dey (64) condensed various phenols with acetonedicarboxylic acid ester and made a systematic study of the reactivity of the coumarin-4-acetic acids thus synthesized: Clayton (48) found that the phenols with alkyl, hydroxy, and dialkylamino groups in the positions marked X in the formulas given below undergo condensa-x^Noh V…”
Section: Azy /mentioning
confidence: 99%
“…Optical excitation is provided by a high pressure Hg lamp using Schott filters UG 11. 7-chlorocoumarin (CC) and 7-bromocoumarin (BC) have been synthesized according to [16]. Doping mate¡ such as CC and BC and coumarin have been purified by recrystallisation and sublimation, host materials p-dibromobenzene (DBB) and durene have been extensively zone refined.…”
Section: Methodsmentioning
confidence: 99%
“…The precursor 4-methyl-substituted coumarins, viz. 4-methyl, 28 6-chloro-4-methyl, 29 7-chloro-4-methyl, 30 Fig. 6 The crystal packing diagram of 6-fluoro-4-formylcoumarin 5.…”
Section: Experimental Synthesis Of the 4-formylcoumarins 1-6mentioning
confidence: 99%